The Influence of Local Original Revenue and Capital Expenditure on the Financial Performance of District/City Governments in Central Sulawesi Province in 2019-2023 - Afgymnastiardin, Afgymnastiardin; Masdar, Rahma; Chairil Furqan, Andi; Masrudin, Masrudin; Meldawati, Lucyani (International Journal of Social Science, Education, Communication and Economics, 2025)
Performance is an achievement that can be achieved by an organization within a certain period of time. Regional financial performance or regional capacity is one measure that can be used to see the ability of a region to run the regional economy. This study aims to determine and analyze the effect of regional original income and capital expenditure on regional financial performance, as well as to determine which variables have the most dominant influence on regional financial performance in districts/cities in Central Sulawesi province. The data processed is secondary data from the annual reports of districts/cities in Central Sulawesi province for 2019-2023 which were taken with total sampling. The method used in this study is the multiple linear regression analysis method using the SPSS 25 application. The results of this study indicate that: regional original income does not have a significant effect on regional financial performance and capital expenditure has a negative and significant effect on regional financial performance.